High performance as-cast semitransparent polymer solar cells. Issue 11 (28th February 2018) - Huang, He; Li, Xiaojun; Zhong, Lian; Qiu, Beibei; Yang, Yankang; Zhang, Zhi-Guo; Zhang, Zhanjun; Li, Yongfang
Abstract : Semi-transparent polymer solar cells (ST-PSCs) were fabricated with PTB7-Th as donor and ITVfIC as acceptor, and the as-cast ST-PSC shows a higher efficiency of 8.21% with AT of 33.7%. Abstract : Semi-transparent polymer solar cells (ST-PSCs) have attracted great attention recently because of their potential for application in smart windows, etc. Here, we fabricated ST-PSCs based on a low band-gap conjugated polymer, PTB7-Th, as the donor and a narrow band-gap n-type organic semiconductor (n-OS), ITVfIC, as the acceptor. The active layer (with a thickness of 100 nm) of the ST-PSC exhibits a high average transmittance (AT) of 73.46% in the wavelength range of 400–600 nm. The as-cast ST-PSC with 15 nm Ag as the cathode without any additive or thermal-annealing treatment shows a higher power conversion efficiency (PCE) of 8.21% with an AT of 33.7%, which is one of the highest values for ST-PSCs without extra treatment. In addition, the ST-PSCs show good thermal stability with 91% of their original PCE value retained after high temperature treatment at 200 °C for 2 hours. The higher PCE and good stability indicate that the ST-PSC has potential for practical application and the narrow bandgap ITVfIC could be a promising n-OS acceptor for the fabrication of ST-PSCs.